2019
DOI: 10.1515/nanoph-2019-0379
|View full text |Cite
|
Sign up to set email alerts
|

Strongly coupled, high-quality plasmonic dimer antennas fabricated using a sketch-and-peel technique

Abstract: A combination of helium- and gallium-ion beam milling together with a fast and reliable sketch-and-peel technique is used to fabricate gold nanorod dimer antennas with an excellent quality factor and with gap distances of less than 6 nm. The high fabrication quality of the sketch-and-peel technique compared to a conventional ion beam milling technique is proven by polarisation-resolved linear dark-field spectromicroscopy of isolated dimer antennas. We demonstrate a strong coupling of the two antenna arms for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…Hence, a nanopatterning approach that is able to realize sub-10 nm gaps in a reproducible manner is highly desired. He ion beam milling already demonstrated these capabilities in the fabrication of strongly coupled dimers with gap distances of less than 6 nm [ 62 64 ]. In all previous cases, the antenna shapes were pre-fabricated with Ga ion beam milling or lithographic approaches and only single-line cuts were performed with He ions to create dimer antennas.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a nanopatterning approach that is able to realize sub-10 nm gaps in a reproducible manner is highly desired. He ion beam milling already demonstrated these capabilities in the fabrication of strongly coupled dimers with gap distances of less than 6 nm [ 62 64 ]. In all previous cases, the antenna shapes were pre-fabricated with Ga ion beam milling or lithographic approaches and only single-line cuts were performed with He ions to create dimer antennas.…”
Section: Resultsmentioning
confidence: 99%
“…[143] A number of variations to the SPL procedure have been reported. [144][145][146][147][148] For instance, instead of using a negative resist, it is possible to directly create nano-trenches in a deposited metal film by FIB milling before selectively removing the metal outside of the trenches by peeling, see Figure 14. [142] In the case of a silicon substrate, it has been shown that slight over-milling of the unwanted metal causes a thin layer of silicon atoms to be sputtered onto the side walls of the retained metal, which serves to protect the retained metal from damage during the subsequent peeling step.…”
Section: Peeling-based Methodsmentioning
confidence: 99%
“…In comparison, gallium FIB milling produced gap widths larger than 20 nm, V-shaped side walls, rounded edges and a perturbed top surface. By optimizing the gold film itself to enable more uniform milling rates, for example, by increasing the grain sizes in polycrystalline films by annealing [ 179 180 ], or by using single-crystal gold [ 181 ], further improvements in both gap size and reproducibility can be achieved. Additional plasmonic structures that have been fabricated by helium FIB milling include trimeric assemblies of resonant nanoapertures [ 182 ], arrays of nanostructured radial resonant apertures [ 183 ], and plasmonic heptamer nanohole arrays [ 139 ] ( Figure 6h ), all in gold films, as well as multiresonant plasmonic nanoslit cavities [ 184 ] and plasmonic tetramer nanoantennae [ 51 ] in crystalline gold platelets.…”
Section: Reviewmentioning
confidence: 99%
“…Compared with the gallium FIB, sketch-and-peel using the helium FIB enables finer cuts and, in the first demonstrations, the fabrication of arrays of plasmonic dimer structures with a gap size of 15 nm was achieved [ 186 ]. Subsequent iterations of the method routinely report gap sizes of 5 nm [ 180 181 ], including the fabrication of heart-shaped nanodimers defined using a shared boundary in the center to create the nanogap as opposed to milling the dimer outline and gap separately [ 140 ] ( Figure 6i ). To further increase the efficiency of the process, a combination of gallium and helium FIB milling can be applied, the former for the coarser outlines and the latter for the fine cuts forming the nanogaps [ 180 , 187 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation